Energy system contributions to the special judo fitness test - Franchini, E.; Sterkowicz, S.; Szatlan-Gabrys, U.; Gabrys, T.; Garnys, M. (International Journal of Sports Physiology and Performance, 2011)
Purpose: This study investigated the energy system contributions of judo athletes to the Special Judo Fitness Test (SJFT). Methods: Fourteen male judo athletes performed the SJFT, which comprised three periods of judo activity (A = 15 s, B and C = 30 s) interspersed with 10 s rest intervals. During this test, one athlete threw two others positioned 6 m from each other using the ippon-seoi-nage technique. The fractions of the aerobic, anaerobic alactic and anaerobic lactic systems were calculated based on oxygen uptake, the fast component of excess postexercise oxygen uptake, and changes in net blood lactate, respectively. The contribution of the three energy systems was compared using a repeated measures analysis of variance and Bonferroni`s multiple comparisons test. Compound symmetry, or sphericity, was determined by Mauchly`s test. A level of significance of 5% (P < .05) was adopted in all analyses. Results: The alactic energy system presented a higher (F = 20.9; P < .001; power observed = 1.0) contribution (86.8 ± 23.6 kJ; 42.3 ± 5.9%) during the test when compared with both aerobic (57.1 ± 11.3 kJ; 28.2 ± 2.9%) and lactic (58.9 ± 12.1 kJ; 29.5 ± 6.2%) energy systems (P < .001 for both comparisons). Conclusions: The higher alactic contribution seems to be a consequence of the high-intensity efforts performed during the test, and its intermittent nature. Thus, when using the SJFT, coaches are evaluating mainly their athletes` anaerobic alactic system, which can be considered to be the most predominant system contributing to the actions (techniques) performed in the match.